Factors affecting willingness to comply with public health measures during the pandemic among sub-Sahara Africans - Nwaeze, O.; Langsi, R.; Osuagwu, U.L.; Oloruntoba, Richard; Ovenseri-Ogbomo, G.O.; Abu, E.K.; Timothy Chikasirimobi, G.; Charwe, D.D.; Ekpenyong, B.; Mashige, K.P.; Goson, P.C.; Ishaya, T.; et al. (MAKERERE UNIV, COLL HEALTH SCIENCES,SCH MED, 2021)
Background: The unprecedented outbreak of coronavirus disease (COVID-19) drastically spread worldwide, resulting in extraordinary measures put in place in various countries including Sub Saharan Africa (SSA) countries. Objective: To assess the factors associated with compliance with the public health measures imposed by various SSA countries. Method: Cross sectional study using self-administered surveys distributed on social media platforms between April 18th and May 16th, 2020, corresponding with the mandatory lockdown period in most SSA countries. Multivariate analysis examined the associated factors. Results: The prevalence of hand hygiene, quarantine, self isolation practices, wearing of face mask and attending large gatherings during COVID-19 were 94%, 39%, 31%, 64% and 14%, respectively. In multivariate models, older age 49+ years: adjusted OR 2.13, 95%CI 1.22,3.71), females (OR 1.41,95%CI 1.03,1.93), Central African countries (OR 3.73,95%CI 2.02,6.87) were associated with wearing face mask. Living alone (aOR 1.52,95%CI 1.04,2.24) during the lockdown was associated with avoiding large gatherings including religious events. Female respondents (aOR 1.61, 95%CI 1.30, 2.00), married (aOR 1.71,95%CI 1.33,2.21) and unemployed (aOR 1.62,95%CI 1.25,2.09) SSAs were more likely to practice self-quarantine measures. Conclusion: The low prevalence of mitigation practices suggest the need for targeted education campaign programs to sensitise the population.